(untitled) (Journal of Dentistry and Allied Science, 2023)
Background and Aim: Mycobacterium tuberculosis is the causative agent of tuberculosis (TB). Bangladesh is one of the nations with a high TB burden, and the number of cases and fatalities from the disease are rising constantly. Analyzing the serum levels of IL-6 of TB patients may be helpful to track the development of infection and determine the likelihood that the disease will progress to an active phase. The goal of the current study was to assess the serum level of IL-6 in tuberculosis patients. Methods: This case control study was conducted at the Department of Biochemistry, National Medical College and Hospital, Dhaka during November 2017 to November 2020. This study contained two groups, one with 50 controls who had no active infections and another with 50 patients who had been diagnosed with active pulmonary tuberculosis. Serum levels of IL-6 were assessed prior to, during, and after anti-tubercular therapy in patients with active pulmonary TB and also in control individuals. Chemiluminescence assay was used to evaluate the serum levels of IL-6 in all subjects. Results: In contrast to patients undergoing therapy, patients completing treatment, and control subjects, patients with active TB had mean serum levels of IL-6 which were significantly higher (p < 0.01). On top of that, it was found that IL-6 levels in TB patients both during and after therapy were significantly higher than in controls (p < 0.05). Conclusion: A strong biomarker of tuberculosis may be IL-6, which appears to be a predominant cytokine produced during mycobacterial infection and which also plays a part in clinical symptoms and pathological outcomes of this disease. Journal of Dentistry and Allied Science, Vol. 6 No 1: 8-12